The Growth of Mobile Learning Applications in Language Education: A Bibliometric Overview - Hunowu, Merlindawati; Mohamad, Wiranti; Akhmad, Enni (Journal of English Teaching and Linguistic Issues (JETLI), 2023)
The rapid advancement of mobile technology has transformed education, with mobile learning applications (m-learning) becoming integral to language education. This study provides a bibliometric analysis of research on mobile learning applications in language education, examining trends, types of research, and key themes from 2010 to 2023. Data were collected from major academic databases, including Scopus, Web of Science, SINTA, and Google Scholar, using keywords related to mobile learning and language education. The findings reveal a significant increase in publications over the past five years, reflecting the growing academic interest in m-learning. Qualitative research methods have been predominantly used, focusing on user experiences and the contextual nature of mobile learning. Critical thinking skills have emerged as a key area of focus, indicating a shift towards using mobile learning for deeper cognitive processes. The study also highlights the central role of students as research subjects, while noting a gap in research on other stakeholders, such as teachers and administrators. Data collection has primarily relied on tests to measure cognitive outcomes, but the study suggests incorporating a variety of methods to capture a more holistic view of the learning experience. The conclusion emphasizes the need for ongoing research to optimize the use of mobile learning applications in language education, advocating for a broader inclusion of stakeholders and diverse research methodologies. This bibliometric overview contributes to the understanding of mobile learning's impact on language education and offers insights for future research directions.